2003
DOI: 10.1007/s00894-003-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

Homology model of human corticosteroid binding globulin: a study of its steroid binding ability and a plausible mechanism of steroid hormone release at the site of inflammation

Abstract: Corticosteroid binding globulin (CBG) and thyroxin binding globulin (TBG) both belong to the same SERPIN superfamily of serine-proteinase inhibitors but in the course of evolution CBG has adapted to its new role as a transport agent of insoluble hormones. CBG binds corticosteroids in plasma, delivering them to sites of inflammation to modify the inflammatory response. CBG is an effective drug carrier for genetic manipulation, and hence there is immense biological interest in the location of the hormone binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The alignment of pig and rat amino acid sequences shows that the pig Arg307 amino acid is located at two residues of the substitution Met276Ile in the rat that is implicated in reduced steroid binding affinity of the BioBreeding rat (Smith and Hammond 1991). According to the deduced tertiary structure of CBG (Dey and Roychowdhury 2003), amino acids Gln232, Asn238, Ile263, and Trp266 seem involved in ligand binding in humans and are well conserved across species. In our pig model, Thr257Met and Ile265Val are very close to these important amino acids and within the b-barrel, which has been involved in steroid binding (Dey and Roychowdhury 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alignment of pig and rat amino acid sequences shows that the pig Arg307 amino acid is located at two residues of the substitution Met276Ile in the rat that is implicated in reduced steroid binding affinity of the BioBreeding rat (Smith and Hammond 1991). According to the deduced tertiary structure of CBG (Dey and Roychowdhury 2003), amino acids Gln232, Asn238, Ile263, and Trp266 seem involved in ligand binding in humans and are well conserved across species. In our pig model, Thr257Met and Ile265Val are very close to these important amino acids and within the b-barrel, which has been involved in steroid binding (Dey and Roychowdhury 2003).…”
Section: Discussionmentioning
confidence: 99%
“…According to the deduced tertiary structure of CBG (Dey and Roychowdhury 2003), amino acids Gln232, Asn238, Ile263, and Trp266 seem involved in ligand binding in humans and are well conserved across species. In our pig model, Thr257Met and Ile265Val are very close to these important amino acids and within the b-barrel, which has been involved in steroid binding (Dey and Roychowdhury 2003).…”
Section: Discussionmentioning
confidence: 99%
“…CBG has a single steroid-binding site with high affinity to glucocorticoids, such as cortisol in humans and corticosterone in rat (Dey and Roychowdhury 2003;Hammond et al 1991;Demey-Ponsart et al 1982), while dexamethasone does not bind to CBG (Lindenbaum and Chatterton 1981). We observed CBG in neuroendocrine hypothalamic neurons, hippocampal pyramidal cells, and cerebellar neurons (Möpert et al 2006;Sivukhina et al 2006).…”
Section: Introductionmentioning
confidence: 66%
“…Several studies suggest the existence of a membrane associated receptor for CBG (Maitra et al 1993;Dey and Roychowdhury 2003). The role of such receptors has not been completely defined, but it is possible that they aid in capturing and/or internalizing CBG.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a photoaffinity labeling study in which it was found that a tryptophan residue, #371, was selectively labeled by various ligands (14), the ligand binding site was proposed to involve residues near the carboxyl end of the protein. Finally, models have been proposed (15,16), in which, if there is any cysteine involved in the binding site, it would have to be Cys 228.…”
Section: Introductionmentioning
confidence: 99%